Outsourcing w ochronie zdrowia - Kowalewski, Marcin (Outsourcing in Polish Health Care System, 2005)
This article explains the role of outsourcing in Polish hospitals. Outsourcing is when a hospital purchases a product or process from an outside supplier rather than producing in house. There are few reasons to use outsourcing in health care:• reduce costs and staff,• increase productivity and throughput by focusing on core products. Outsorcing should be a part of the restructuralisation of Polish hospitals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 401-406